Lumbosacral Radiculoplexus Neuropathy: Neurologic Outcomes and Survival in a Population-Based Study. (20th April 2021) - Pinto, Marcus V.; Ng, Peng-Soon; Howe, Benjamin M.; Laughlin, Ruple S.; Thapa, Prabin; Dyck, Peter J.; Dyck, P. James B.
Abstract : Objective: To determine whether patients in the community with lumbosacral radiculoplexus neuropathy (LRPN) have milder neuropathy than referral patients, we characterized the outcomes and survival of population-based compared to referral-based LRPN cohorts. Background: Previously, we found that the incidence of LRPN is 4.16/100, 000/y, a frequency greater than other inflammatory neuropathies. The survival of patients with LRPN is uncharacterized. Methods: Sixty-two episodes in 59 patients with LRPN were identified over 16 years (2000–2015). Clinical findings were compared to previous referral-based LRPN cohorts. Survival data were compared to those of age- and sex-matched controls. Results: At LRPN diagnosis, median age was 70 years, median Neuropathy Impairment Score (NIS) 22 points, 92% had pain, 95% had weakness, 23% were wheelchair-bound, and median modified Rankin Scale score (mRS) was 3 (range 1–4). At last follow-up, median NIS improved to 17 points ( p < 0.001) with 56% having ≥4 points improvement, 16% were wheelchair-bound, and median mRS was 2. Compared to referral-based LRPN cohorts, community patients with LRPN had less impairment, less bilateral disease (37% vs 92%), and less wheelchair usage (23% vs 49%). LRPN survival was 86% at 5 years and 55% at 10 years. Compared to age- and sex-matched controls, patients with LRPN had 76% increased risk of death ( p = 0.016). In multivariate analysis, diabetes, age, stroke, chronic kidney disease, peripheral artery disease, and coronary artery disease were significant mortality risk factors but LRPN was not. Conclusion: LRPN is a painful, paralytic, asymmetric, monophasic, sometimes bilateral pan-plexopathy that improves over time but leaves patients with impairment. Although having LRPN increases mortality, this increase is probably due to comorbidities (diabetes) rather than LRPN itself.